Improving the Development of SMEs in the Batik Industry in Pekalongan - Mariana Febrianti, R. Adjeng; Ramadhan , Bani Ady (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study was to describe consumer perceptions of customer relationship management (CRM), product differentiation, and price on purchasing decisions for batik Pekalongan. Design / methodology / approach: The technique used in this research is the Structural Equation Model/SEM. The primary data of this study were obtained from questionnaires and interviews with 150 respondents. Findings: The results of the study concluded that CRM, product differentiation, and price have an influence on purchasing decisions of Batik Pekalongan. Research limitations/implications: This study is proposed to fill research gaps while emphasizing the importance of CRM, product differentiation and price factors on purchasing decisions for SMEs in Indonesia, especially Pekalongan City. These three factors play an important role for the sustainability of SMEs in building creativity and innovation so that they are expected to make a positive contribution to business sustainability, especially SMEs.